The Development And Validity Of A Mobile Application For Preventing 30 Days Re-Admission Among Heart Failure Patients - Amalia, Irma Nur (Journal of health research and technology, 2024)
Objective: To create and validate the expert validity evidence and content of a prototype mobile application for preventing 30 days readmission among heart failure patients. Method: Examination of technology advancement from the perspective of contextualized instructional design. During the analysis phase, five patients participated in a qualitative study and scope review to determine the content that would be included in the application. In the validation stage, cardiologist, specialist nurses and IT expert evaluated the content through face validity assessment. Data were analyzed using descriptive statistics. Results: The prototype of the application, called “Tele-Heart Nursing Care” has an interface and free navigation screens covering the Daily Monitoring for heart failure patients include Vital sign and Sign-Symptom monitoring, adherence of diet, exercise and medication. The app also features an educational guide, resources for early recognition of clinical signs, do's and don'ts to prevent the risk of relapse. The consultation feature is also available in a wide selection of themes for patients to choose from. Both the target audience and experts found the technology to be sufficient. Conclusion: It was feasible to create and verify the look and content of the “Tele-Heart Nursing Care” application prototype, which demonstrates the potential to promote self-care in people with heart failure